Teaching Techniques, Types of Personality, and English Listening Skill - Ni Made Ratminingsih (Universitas Negeri Malang, 2013)
Abstract: Teaching Techniques, Types of Personality, and English Listening Skill. This study investigated the effect of teaching techniques and types of personality on English listening skill. This experimental study involved 88 students under investigation, which were determined randomly through multi-stage random sampling technique. The results of the research indicate that there is an interaction effect between the teaching techniques and types of personality on the English listening skill; there is no significant difference in the listening skill between the group of students who learn using the game technique and those who learn using the song technique; the listening skill of students having extrovert personality is better than those having introvert personality; the listening skill of students having extrovert personality who learn using the game technique is lower than those who learn using the song technique; and the listening skill of students having introvert personality who learn using the game technique is higher than those who learn using the song technique. Abstrak: Teknik Pembelajaran, Tipe Kepribadian, dan Keterampilan Mendengarkan Bahasa Inggris. Penelitian ini bertujuan untuk mengetahui pengaruh teknik pembelajaran dan tipe kepribadian terhadap keterampilan mendengarkan bahasa Inggris. Penelitian ini melibatkan 88 orang siswa, yang ditentukan secara acak melalui multi stage random sampling technique. Hasil penelitian menunjukkan bahwa terdapat pengaruh interaksi antara teknik pembelajaran dan tipe kepribadian terhadap keterampilan mendengarkan bahasa Inggris; tidak terdapat perbedaan yang signifikan pada keterampilan mendengarkan antara siswa yang belajar dengan teknik pembelajaran permainan dan lagu; keterampilan mendengarkan siswa yang berkepribadian ekstroversi lebih baik daripada yang berkepribadian introversi; keterampilan mendengarkan siswa yang berkepribadian ekstroversi, yang belajar dengan teknik pembelajaran permainan lebih rendah daripada yang belajar dengan teknik pembelajaran lagu; dan keterampilan mendengarkan siswa yang berkepribadian introversi, yang belajar dengan teknik pembelajaran permainan lebih tinggi daripada yang belajar dengan teknik pembelajaran lagu.